Optimasi Formula dan Uji Evaluasi Sediaan Kondisioner Ekstrak Minyak Zaitun (olive oil) - Jannah, Nadia Miftahul; Anggraini, Yessy Dwi (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Conditioner is a product that consumers need in everyday life as hair care. One of the active substances commonly used as a moisturizer is olive oil which is obtained from olives. The largest content of olive oil is oleic acid, oleic acis provides properties that can retain moisture. The aim of this research was to determine the formulation of olive oil extract conditioner using the SLD method, as well as to determine the result of the physical evaluation. Methods: Determination of the difference in concentrations of hydroxyethylcellulose and propylene Glycol using the Simplex Latex Design (SLD) method. The result Physical evaluation includes organileptic tests, test homogeneity, pH test, viscosity tets and stability test. After testing 8 formulas, optimal result were obtained, namely hydroxyethylcellulose 1,78 g and propylene Glycol 28,23 g. The stability test result show that the three formulas are stable as seen from the good organileptic and homogeneity test result with the A/M dosage type. The three formulas have a pH of 4,34, 4,47 and 4,71 and a viscosity value of R1, namely 6408, R2 7932, R3 namely 9408, which meets the requirement. Conclusion: The optimum formula was obtained from the concentration ratio, namely hydroxyethylcellulose 1,78 g and propylene Glycol 28,24 g.